A STUDY OF INFANTICIDES IN IMPHAL DURING THE PERIOD 2007-2011 (A 5 YEAR STUDY) (Journal of Forensic Medicine & Toxicology, 2013)
The study was conducted in the Dept. of Forensic Medicine, Regional Institute of Medical Sciences,Imphal during the 5 yr period, from 2007-2011. Out of a total of 2463 post mortem examinations, there were only 9 cases of infant deaths. 4 were males, 4 females and in 1 the sex could not be identified as the perineum was destroyed by decomposition. 5 were born full term and the rest were preterm. 3 were live born, and 6 were stillborn. 1 had congenital bilateral cleft lip and palate with polydactyly. In 6 cases, the cord was tied whereas in 3 cases, the cord was not tied. 3 were positive for hydrostatic test and the rest were negative. Regarding place of recovery, 1 was abandoned in a hospital, 1 from a river, 1 from a roadside, 1 in the garbage, 1 in a drain, 1 from a swamp and 1 from a rural roadside. The cause of death was head injury in 3 cases, in 1 case, hypothermia and lack of nutrition (abandoned congenitally defective baby) was the cause of death, and in the rest the babies were stillborn with no known cause of death. Regarding mode of disposal, 2 were wrapped in polythene bags, 2 were left naked, 1 in a gunny bag, 3 were wrapped in cloth pieces and 1 was left in a cardboard box. This study was conducted to find out whether there was any sex bias and to suggest preventive measures.
Keywords: Infanticide; Gender bias; Abandoned babies